Medication-related experiences of patients with polypharmacy: a systematic review of qualitative studies - Anne Frølich; Christian Ulrich Eriksen; Stavros Kyriakidis; Line Due Christensen; Ramune Jacobsen; Jannie Laursen; Mikkel Bring Christensen (BMJ Open)
Background We aimed to synthesise qualitative studies exploring medication-related experiences of polypharmacy among patients with multimorbidity.Methods We systematically searched PubMed, Embase and Cumulative Index to Nursing and Allied Health Literature in February 2020 for primary, peer-reviewed qualitative studies about multimorbid patients’ medication-related experiences with polypharmacy, defined as the use of four or more medications. Identified studies were appraised for methodological quality by applying the Critical Appraisal Skills Programme checklist for qualitative research, and data were extracted and synthesised by the meta-aggregation approach.Results We included 13 qualitative studies, representing 499 patients with polypharmacy and a wide range of chronic conditions. Overall, most Critical Appraisal Skills Programme items were reported in the studies. We extracted 140 findings, synthesised these into 17 categories, and developed five interrelated syntheses: (1) patients with polypharmacy are a heterogeneous group in terms of needing and appraising medication information; (2) patients are aware of the importance of medication adherence, but it is difficult to achieve; (3) decision-making about medications is complex; (4) multiple relational factors affect communication between patients and physicians, and these factors can prevent patients from disclosing important information; and (5) polypharmacy affects patients’ lives and self-perception, and challenges with polypharmacy are not limited to practical issues of medication-taking.Discussion Polypharmacy poses many challenges to patients, which have a negative impact on quality of life and adherence. Thus, when dealing with polypharmacy patients, it is crucial that healthcare professionals actively solicit individual patients’ perspectives on challenges related to polypharmacy. Based on the reported experiences, we recommend that healthcare professionals upscale communicative efforts and involve patients’ social network on an individualised basis to facilitate shared decision-making and treatment adherence in multimorbidpatients with polypharmacy.